2005
DOI: 10.1111/j.1447-0756.2005.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Ureaplasma urealyticum colonization might be associated with increased incidence of preterm delivery in pregnant women without prophlogistic microorganisms on routine examination

Abstract: Cervical U. urealyticum colonization might be associated with preterm labor and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
2
23
0
1
Order By: Relevance
“…Indeed, Holst et al, demonstrated that the presence of U urealyticum in cervical fluid was associated with higher levels of IL-6in the vaginal fluid [5]. Moreover, recent case-control studies using PCR methods indicated that cervico-vaginal mycoplasma colonization might be associated with preterm birth [16,17]. Investigators suggested that the density of colonization [18] or some specific biovar [19] may be associated with preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Holst et al, demonstrated that the presence of U urealyticum in cervical fluid was associated with higher levels of IL-6in the vaginal fluid [5]. Moreover, recent case-control studies using PCR methods indicated that cervico-vaginal mycoplasma colonization might be associated with preterm birth [16,17]. Investigators suggested that the density of colonization [18] or some specific biovar [19] may be associated with preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Mitsunari et al [11] findings support the association between cervical U. urealyticum and preterm delivery (controls colonisation 46% compared to 87% in preterm delivery patients).…”
Section: Ureaplasma Sppmentioning
confidence: 78%
“…Ureaplasma genital tract colonization has been associated with adverse pregnancy outcomes such as spontaneous abortion [10], premature rupture of membranes (PROM) [4], premature delivery [11], neonatal morbidity and perinatal death [12]. The methodology and samples vary considerably between studies, which makes combining and synthesizing the result difficult.…”
Section: Ureaplasma Sppmentioning
confidence: 99%
“…in amniotic fluid was associated neither with a different pregnancy outcome nor with the magnitude of the intraamniotic inflammatory response (7). Mitsunary et al showed that the difference between biovars in the cervix did not influence the evidence of preterm labor (10). A high density vaginal colonization with Uu.…”
Section: Discussionmentioning
confidence: 99%